Enhancement of Ethanol Production in Electrochemical Cell by Saccharomyces cerevisiae (CDBT2) and Wickerhamomyces anomalus (CDBT7) - Joshi, Jarina; Dhungana, Pradip; Prajapati, Bikram; Maharjan, Rocky; Poudyal, Pranita; Yadav, Mukesh; Mainali, Milan; Yadav, Amar Prasad; Bhattarai, Tribikram; Sreerama, Lakshmaiah (Frontiers in Energy Research, 2019)
Bioethanol (a renewable resource), blended with gasoline, is used as liquid transportation fuel worldwide and produced from either starch or lignocellulose. Local production and use of bioethanol supports local economies, decreases country's carbon footprint and promotes self-sufficiency. The latter is especially important for bio-resource-rich land-locked countries like Nepal that are seeking alternative transportation fuels and technologies to produce them. In that regard, in the present study, we have used two highly efficient ethanol producing yeast strains, viz., Saccharomyces cerevisiae (CDBT2) and Wickerhamomyces anomalous (CDBT7), in an electrochemical cell to enhance ethanol production. Ethanol production by CDBT2 (anodic chamber) and CDBT7 (cathodic chamber) control cultures, using 5% glucose as substrate, were 12.6 ± 0.42 and 10.1 ± 0.17 mg·mL−1 respectively. These cultures in the electrochemical cell, when externally supplied with 4V, the ethanol production was enhanced by 19.8 ± 0.50% and 23.7 ± 0.51%, respectively, as compared to the control cultures. On the other hand, co-culturing of those two yeast strains in both electrode compartments resulted only 3.96 ± 0.83% enhancement in ethanol production. Immobilization of CDBT7 in the graphite cathode resulted in lower enhancement of ethanol production (5.30 ± 0.82%), less than free cell culture of CDBT7. CDBT2 and CDBT7 when cultured in platinum nano particle coated platinum anode and neutral red-coated graphite cathode, respectively, ethanol production was substantially enhanced (52.8 ± 0.44%). The above experiments when repeated using lignocellulosic biomass hydrolysate (reducing sugar content was 3.3%) as substrate, resulted in even better enhancement in ethanol production (61.5 ± 0.12%) as compared to glucose. The results concluded that CDBT2 and CDBT7 yeast strains produced ethanol efficiently from both glucose and lignocellulosic biomass hydrolysate. Ethanol production was enhanced in the presence of low levels of externally applied voltage. Ethanol production was further enhanced with the better electron transport provision i.e., when neutral red was deposited on cathode and fine platinum nanoparticles were coated on the platinum anode.